Cut-off values of skeletal muscle index and psoas muscle index at L3 vertebra level by computerized tomography to assess low muscle mass - Bahat, Gulistan; Turkmen, Banu Ozulu; Aliyev, Samil; Catikkas, Nezahat Muge; Bakir, Baris; Karan, Mehmet Akif (Clinical nutrition (Edinburgh, Scotland), 2021)
Computerized tomography (CT) is considered the gold standard for the evaluation of total skeletal muscle quantity. Skeletal muscle assessments at the L3 vertebra level revealed significantly correlated with total body muscle measurements. Clinicians need cut-offs to evaluate low muscle mass in various patients who already had CT imaging without any additional cost. This assessment is important to help the physicians to stratify the patients for mortality and other complications. It may also enable the diagnosis of malnutrition by the GLIM criteria. Few studies reported cut-offs in different populations. We aimed to provide cut-off values for total skeletal muscle index (SMI) and psoas muscle mass index (PMI) at the L3 vertebra level in the Turkish population. We assessed the preoperative plain CT images of living adult liver donors who were admitted to a single transplantation center between June 2010 and April 2018. We derived cut-off values with two alternative methods, the 5th percentile value or mean minus two standard deviations and from two groups of study participants, i.e. the total study population and the younger subgroup aged between 18 and 40. The study population involved 601 subjects with a mean age of 32.5 ± 9 (range: 18–59 years) and 326 (54.2%) was male. The younger subgroup was composed of 482 individuals with a mean age of 28.8 ± 5.9 and 55.6% male. In patients aged between 18 and 40, PMI and SMI cut-offs by using the 5th percentile were 5.40 cm2/m2, 41.42 cm2/m2 for males; and 3.56 cm2/m2, 30.70 cm2/m2 for females; respectively. The cut-offs of PMI and SMI by using mean minus two standard deviations were 4.62 cm2/m2, 38.67 cm2/m2 for males; and 2.66 cm2/m2, 27.8 cm2/m2 for females; respectively. These cut-offs were comparable to the other populations. Our study provided cut-offs to be used in CT images for PMI and SMI. There is a need for further longitudinal studies to verify whether these cut-offs are successful in predicting mortality or other adverse outcomes associated with low muscle mass.